2017
DOI: 10.1038/ismej.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

Succession in the petroleum reservoir microbiome through an oil field production lifecycle

Abstract: Subsurface petroleum reservoirs are an important component of the deep biosphere where indigenous microorganisms live under extreme conditions and in isolation from the Earth’s surface for millions of years. However, unlike the bulk of the deep biosphere, the petroleum reservoir deep biosphere is subject to extreme anthropogenic perturbation, with the introduction of new electron acceptors, donors and exogenous microbes during oil exploration and production. Despite the fundamental and practical significance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 52 publications
5
137
0
5
Order By: Relevance
“…The maturation of many producing oil fields in the North Sea is resulting in larger volumes of water both being injected for secondary oil recovery and co-produced during oil extraction (OSPAR Commission, 2000). Produced water discharge could thus be an anthropogenic large-scale dispersal vector for transporting subsurface bacteria into the ocean, since many North Sea oil fields are hot and anoxic and known to harbour anaerobic thermophilic Firmicutes (Rosnes et al, 1991;Nilsen et al, 1996;Gittel et al, 2009;Vigneron et al, 2017).…”
Section: Marine Thermophilic Endospores Seeding the Tyne Estuarymentioning
confidence: 99%
“…The maturation of many producing oil fields in the North Sea is resulting in larger volumes of water both being injected for secondary oil recovery and co-produced during oil extraction (OSPAR Commission, 2000). Produced water discharge could thus be an anthropogenic large-scale dispersal vector for transporting subsurface bacteria into the ocean, since many North Sea oil fields are hot and anoxic and known to harbour anaerobic thermophilic Firmicutes (Rosnes et al, 1991;Nilsen et al, 1996;Gittel et al, 2009;Vigneron et al, 2017).…”
Section: Marine Thermophilic Endospores Seeding the Tyne Estuarymentioning
confidence: 99%
“…The microbial community profiles of the Crossfield and Segno produced waters were analysed in depth alongside the microbial community profiles of produced waters from other oil reservoirs of varying geographical locations and physicochemical characteristics (Table S4). Comparisons were constructed with the raw 16S rRNA amplicon sequence data sets acquired from the NCBI Sequence Read Archive (SRA) and through personal communication (Lewin et al, 2014;Gao et al, 2015;Hu et al, 2016;Shelton et al, 2016;Li et al, 2017;Vigneron et al, 2017). As expected from the nearly identical microbial compositions of the Crossfield and Segno samples, tight clustering was observed for the microbial communities in these samples, regardless of the metrics used for beta diversity calculation (Fig.…”
Section: Comparative Analyses Of Oil Reservoir Microbial Communitiesmentioning
confidence: 99%
“…Since the 1980s, scientific investigations, both culture-based and culture-independent, have been performed to better understand the microbial community structures and metabolic potentials in developed oil reservoirs (Mueller and Nielsen, 1996;Orphan et al, 2000Orphan et al, , 2003. More recently, high-throughput sequencing techniques (e.g., pyrosequencing and Illumina HiSeq/MiSeq sequencing technologies) have been implemented to analyse the microbial community compositions and metagenomes of oil reservoirs Lewin et al, 2014;Frank et al, 2016;Hu et al, 2016;Vigneron et al, 2017). These investigations have demonstrated that stable active microbial populations are established in the subsurface oil reservoirs with temperatures up to 80°C and even higher, and also that anthropogenic alterations, for example injection of nitrate to treat souring, may lead to perturbation of the indigenous microbial populations and their metabolic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In oil fields nitrate‐driven sulfur oxidation is promoted when nitrate is added externally as a reservoir souring control strategy (Vigneron et al ., ). The sulfide‐oxidizing and nitrate‐reducing ability of Sulfurimonas spp.…”
Section: Introductionmentioning
confidence: 97%
“…and similar sulfide‐oxidizing, nitrate‐reducing microorganisms can have major impacts on industrial processes. Stimulation of this activity has been explored for mitigation of oil field souring and corrosion control in large‐scale bioengineering strategies in oil fields (Telang et al ., ; Bødtker et al ., ; Shartau et al ., ; Gittel et al ., ; Vigneron et al ., ; Carlson and Hubert, ). Despite one goal of nitrate injection being corrosion control in oil fields (Hubert et al ., ; Lahme et al ., ), S 0 and other potentially corrosive sulfur compounds are often formed and excreted as intermediates during microbial sulfide oxidation (Brune, ; Frigaard and Dahl, ; Lahme et al ., ).…”
Section: Introductionmentioning
confidence: 99%